HUMAN RESOURCE COMPETENCY DEVELOPMENT OF STATE CIVIL APPARATUS (ASN) AT THE BIAK SEARCH AND RESCUE OFFICE - Budi Prasetyo, Endro; Iriawan, Hermanu; Utami, Ayu Kurnia (Gema Kampus IISIP YAPIS Biak, 2025)
This study aims to analyze the development of human resource competencies of State Civil Apparatus (ASN) at the Biak Class A Search and Rescue Office. The research focuses on competency development strategies, supporting and inhibiting factors, and their impact on organizational performance. This qualitative research employed in-depth interviews, observations, and document studies involving structural and functional officials, ASN staff, and relevant stakeholders. The findings reveal that competency development was carried out through technical training, formal education, and on-the-job training. However, challenges persist, such as budget limitations, training facility constraints, individual awareness, and suboptimal competency mapping. Law No. 20 of 2023 on State Civil Apparatus mandates every government institution to prepare an annual competency development plan. Recommendations include increasing budget allocation for training, systematic competency mapping, and implementing reward systems to enhance ASN motivation. Effective competency development is expected to strengthen the Biak Search and Rescue Office’s capability in conducting rescue missions optimally, effectively, and efficiently..